2011
DOI: 10.1007/s00198-011-1588-z
|View full text |Cite
|
Sign up to set email alerts
|

Hypovitaminosis D as a risk factor of hip fracture severity

Abstract: Although vitamin D levels are not different between patients with intracapsular or extracapsular hip fractures, a more severe vitamin D deficiency seems to be associated to more severe osteoporotic hip fractures. A prior vitamin D supplementation could avoid a higher severity of these fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 27 publications
0
28
1
1
Order By: Relevance
“…Other studies have demonstrated that a low vitamin D level or vitamin D deficiency is associated with increased risks for respiratory diseases such as respiratory tract infections [38,39], chronic bronchitis [40], and chronic obstructive pulmonary disease [41,42], and associated with increased mortality in patients with influenza infection [43] and pneumonia [44]. In addition, vitamin D deficiency is associated with low bone density resulting in increased risks of osteoporotic fractures and physical disabilities [45][46][47]. Taken together, these findings may provide insights into potential mechanisms for the survival benefits from higher levels of vitamin D at baseline.…”
Section: Discussionmentioning
confidence: 98%
“…Other studies have demonstrated that a low vitamin D level or vitamin D deficiency is associated with increased risks for respiratory diseases such as respiratory tract infections [38,39], chronic bronchitis [40], and chronic obstructive pulmonary disease [41,42], and associated with increased mortality in patients with influenza infection [43] and pneumonia [44]. In addition, vitamin D deficiency is associated with low bone density resulting in increased risks of osteoporotic fractures and physical disabilities [45][46][47]. Taken together, these findings may provide insights into potential mechanisms for the survival benefits from higher levels of vitamin D at baseline.…”
Section: Discussionmentioning
confidence: 98%
“…These limits vary from 20 ng/mL (50 nmol/L) [28] to 36 ng/mL (90 nmol/L) [27], depending on the target population and the geographical region where BMD was measured. Similarly, a decrease was observed in the incidence of fractures in individuals with 25(OH)D 3 serum levels greater than 12 ng/mL (30 nmol/L) [30] and the average mean 25(OH)D 3 levels were higher in subjects with less severe fractures compared to those with severe fractures [31]. It is noteworthy that these reference values seem to be the same at which PTH level stabilization occurs [32], i.e ., 25(OH)D 3 levels sufficient to establish the best relationship with BMD and with fracture risks are also responsible for the lower levels of PTH, suggesting an important role of PTH in the process.…”
Section: Vitamin D and Osteoporosismentioning
confidence: 99%
“…At 12 months mortality rates were 14.5% and 13.4%, respectively [27] . However, stratifying treatment to severity of hip fractures may be associated with considerable bias, since a higher degree of fracture displacement is significantly associated with hypovitaminosis D [28] which in turn may affect morbidity and mortality in these patients [7] . Only one retrospective study found a higher cumulative mortality after internal fixation compared to HA [29] .…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, recruitment of most patients in recent studies comparing IF with arthroplasty in hip fracture patients date back a decade or even longer [8][9][10][11]17,18,27,[21][22][23][24][25][26][27][28][29][30][31][32][33][34] . In this regard, improved anaesthesia and modern cementing techniques might explain the difference of our results compared to earlier studies.…”
Section: Discussionmentioning
confidence: 99%